Metadata matters: evaluating the quality of Electronic Theses and Dissertations (ETDs) descriptions in Malaysian institutional repositories - Osman, Raudhah; Yanti Idaya A.M.K.,; Abrizah A., (Malaysian Journal of Library and Information Science, 2023)
This study investigates the quality of metadata records in institutional repositories for Electronic Theses and Dissertations (ETDs) in three Malaysian research universities. The study employs metrics derived from Bruce and Hillmann (2004) to evaluate the completeness, accuracy, and consistency of 1138 metadata records from the three institutional repositories, and utilizes quantitative content analysis to identify variants of Dublin Core metadata elements used to describe ETDs. The study uncovers a range of issues with metadata completeness, accuracy, and consistency, emphasizing the need for standardized systems to ensure quality metadata. By highlighting the importance of quality metadata for ETD collections, the study provides valuable insights for academic libraries in designing and describing ETD collections. Overall, this study sheds light on the current metadata practices and elements used in ETD collections, and underscores the significance of effective metadata management for the dissemination and discoverability of scholarly works.